2022
DOI: 10.3389/fpls.2022.1028101
|View full text |Cite
|
Sign up to set email alerts
|

Food and agricultural wastes-derived biochars in combination with mineral fertilizer as sustainable soil amendments to enhance soil microbiological activity, nutrient cycling and crop production

Abstract: The ever-increasing human population associated with high rate of waste generation may pose serious threats to soil ecosystem. Nevertheless, conversion of agricultural and food wastes to biochar has been shown as a beneficial approach in sustainable soil management. However, our understanding on how integration of biochar obtained from different wastes and mineral fertilizers impact soil microbiological indicators is limited. Therefore, in the present study the effects of agricultural (AB) and food waste deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 72 publications
0
4
0
2
Order By: Relevance
“…observed that there are other hormones such as cytokinins and gibberellic acid, which affect the root shape by increasing its length and development while reducing ethylene levels (Waidmann et al 2019) Additionally, Plazas et al (2019) found that the combination of PGPRs and BR s can improve soil hydration rate by playing a crucial signal between ecological conditions and roots as it has been presented in (Mustafa et al 2023). Hence, when Brassinosteroid is used in conjunction with rhizobacterial strains, plants absorb nutrients and more water from the soil; greatly increasing root absorption area without negative behavior (Mustafa et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…observed that there are other hormones such as cytokinins and gibberellic acid, which affect the root shape by increasing its length and development while reducing ethylene levels (Waidmann et al 2019) Additionally, Plazas et al (2019) found that the combination of PGPRs and BR s can improve soil hydration rate by playing a crucial signal between ecological conditions and roots as it has been presented in (Mustafa et al 2023). Hence, when Brassinosteroid is used in conjunction with rhizobacterial strains, plants absorb nutrients and more water from the soil; greatly increasing root absorption area without negative behavior (Mustafa et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…formou přípravy biocharů, např. [38,39]. Při správném dávkování se jeví tyto postupy jako perspektivní jak z pohledu eliminace řady cizorodých látek (s využitím termických procesů), tak z pohledu obohacení půd organickou hmotou a nutrienty s postupným uvolňováním.…”
Section: Půda/směsunclassified
“…On the one hand, biochar can stimulate the activity of enzymes such as urease and peroxidase, which promote the growth and activity of beneficial bacteria in the soil; in addition, biochar boosts microbial diversity and abundance and enhances the structure of the soil microbial community. By affecting microbial metabolic activities, which include the cycling and transformation processes of elements such as carbon, nitrogen, and phosphorus, biochar has the potential to affect crop development and soil nutrient availability [35]. The effects of biochar on soil respiration are complex, and the type and characteristics of the material can have varying effects on the activity of soil microbes that respire.…”
Section: Co-application Of Biochar and Manure Improve Soil Nutrient R...mentioning
confidence: 99%